Implementation of the Problem Based Learning Strategy in the Subject of Aqidah Morals at Madrasah Tsanawiyah Babussalam, Banjarmasin City - Amin, Muhammad Rasyid (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to determine the implementation of the problem-based learning (PBL) strategy in the Aqidah Akhlak subject at Madrasah Tsanawiyah Babussalam, Banjarmasin City. This research is motivated by the large number of teachers who simply teach about the material in class without relating it to problems that are close to the environment around students. A qualitative approach with field study methods was applied in this research because it will explain how the planning, implementation, and evaluation of the implementation of problem-based learning strategies in the Aqidah Akhlak subject were implemented by MTs Babussalam teachers in Banjarmasin City. The results of this research are that in the planning process, teachers prepare learning plans, formulate problems systematically, and adapt them to the material. Meanwhile, in its implementation, the teacher presents the problem and asks students to discuss and analyze it according to their respective points of view. For the evaluation part, the teacher uses oral and written tests held at the end of the lesson as material for reflection and to determine students' understanding of the material taught. Apart from that, the evaluation shows the effectiveness of using this problem-based learning strategy in the Aqidah Akhlak subject so that it can be applied to other subjects at the Madrasah Tsanawiyah level.